CURRENT DEPOSIT ATTRACTION TRENDS BY BANKS OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The deposit policy of commercial banks of Ukraine has undergone significant changes in recent years. These changes are mainly the result of the impact of macroeconomic indicators and the NBU's monetary policy. Since bank deposits are less risky compared to other methods of investment, there is an annual increase of their number and volume.The purpose of the article: to study the modern deposit policy of commercial banks of Ukraine. The article examines the peculiarities of attracting deposits by commercial banks of Ukraine in modern conditions, taking into account factors influencing the external environment. The reasons for the increase or decrease in deposit rates, the dynamics of deposits of individuals and legal entities in 2020-2023, the structure of deposits (the specific weight of deposits in national and foreign currency, the share of time deposits and demand deposits), the rating of Ukrainian banks by deposit portfolio volumes were analyzed. The influence of NBU monetary policy tools (accounting rate and mandatory reserve norms) on the deposit policy of banks is substantiated, and the main problems of attracting deposits in Ukraine are systematized.In order to stimulate the attraction of bank deposits, in particular time deposits, it is first of all necessary to increase trust to the banking system, create prerequisites for stabilizing the country’s financial system. This requires specific measures from the National Bank of Ukraine and other state bodies, without which the measures of individual banks will have no result. To ensure a stable competitive position, each bank needs to introduce innovative deposit tools, develop loyalty programs and find new (more advanced) service methods.
Keywords: deposits, deposit policy, monetary policy, NBU, term deposits, demand deposits, discount rate, required reserves.